Implications of social media x on students' understanding of civic participation in the context of digital democracy - Fortuna, Dewi; Lutfiana, Rose Fitria; Wibowo, Arif Prasetyo (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2025)
This study is motivated by the growing influence of social media X in shaping students' civic participation patterns in the digital democracy era. The main problem lies in how students understand the meaning of civic participation, the forms of digital participation they engage in and their perceptions of digital ethics in such involvement. The purpose of this research is to analyze in depth students' understanding, participation practices, and ethical considerations in using X as a digital public sphere. This research employed a descriptive qualitative method, with data collected through in-depth interviews, digital observation, and documentation of online content. The findings reveal that students perceive civic participation not only as formal involvement such as elections, but also through discussions, critiques, and digital campaigns. The forms of participation vary from passive actions such as likes and retweets to more creative expressions such as threads, infographics, and hashtag campaigns. Nevertheless, these practices face challenges such as slacktivism, polarization, and regulatory risks associated with Indonesia's ITE Law. These findings highlight the urgent need to strengthen critical digital literacy, foster ethical media practices, and internalize democratic values in civic education, ensuring that students are not only digitally active but also capable of substantive, ethical, and responsible participation in digital democracy